Strategi Komunikasi Customer Relations Untuk Mendapatkan Customer Loyalty (Studi Pada Divisi Relationship Manager Pada Produk Standard Chartered Bank Jakarta) - Mubarokah, Riza Nuraini (Universitas Al Azhar Indonesia, 2024)
AbstractIn the face of increasingly intense business competition in the era of globalization, customer relations communicationstrategy becomes crucial in maintaining and enhancingcustomer loyalty, especially for banking companies likeStandard Chartered Bank Jakarta. This research aims to identify and develop effective communication strategies in the context of the Relationship Manager division in investment products. Through a qualitative approach, this study will delveinto a deep understanding of customer needs and expectationsand how Relationship Managers can meet those expectations.The research will mainly focus on information transparency, security, and reliability of solutions in conveying information about the risks and returns of investment products to customers. It is expected that this research will not onlyprovide theoretical insights but also practical solutions thatcan be implemented by banking companies to enhance the effectiveness of their customer relations communication strategies.